Post-meniscectomy rehabilitation - Ellis Janks (AOSIS, 1983)
Removal of the semi-lunar cartilage/s (menisci) of the knee is a common surgical procedure. Surgeons recognize the importance of an exercise programme supervised by a physiotherapist, in order to obtain the best post-operative rehabilitation. However, the best method of post-operative rehabilitation has been a controversial issue. Controlled studies to determine the relative effectiveness of different treatment regimens are reviewed. Substantial research is being carried out to determine the physiological effects of surgical procedures, subsequent immobilization and different forms of exercise on the leg. These are discussed and considered in formulating the ideal post-meniscectomy rehabilitation programme. The effects and importance of isokinetic exercise is emphasized.